PRODUCTION OF YELLOW WOOD ROOT TEA AS A BLOOD SUGAR STABILIZER - Fatmawati Fatmawati; M Athiah; S Sinulingga; L.O Oswari; Safyudin Safyudin (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Diabetes mellitus is a disease or metabolic disorder that is increasing year by year, characterized by high blood sugar levels as a result of insulin function insufficiency. Diabetes mellitus, which is often referred to as diabetes, is a disease or metabolic disorder that is increasing year by year, characterized by high blood sugar levels as a result of insulin function insufficiency. Treatment is by using drugs. Currently, a treatment using herbal medicine is being developed, one of which is Kayu kuning, where in previous studies it was found that the roots of Kayu kuning can reduce blood glucose levels. This has triggered the Biochemistry and Medical Chemistry section of the Faculty of Medicine to introduce to the public the preparations of this herbal medicine with ready-to-use packaging and the right dosage. The process of making tea is carried out at the Chemical Basic Medicine Laboratory, Faculty of Medicine, Sriwijaya University. About 5.6 kg of yellow wood root, washed and cut into small pieces then dried and ground to obtain a coarse powder (simplicia) of about 2.5 kg. Yellow wood root simplicia is put into tea bags weighing 10 g per bag. One tea bag can be brewed with 200 mL of hot water and drunk once a day. In this service, 250 tea bags were produced which were packaged in 50 packages (5 tea bags/package). The production of this yellow wood root tea has been carried out in the Komplek Azhar Lama, Kenten Laut, Palembang. Keywords: Herbal medicine, yellow root (Arcangelisia flava)